IMPLEMENTASI MANAJEMEN PEMBELAJARAN TERHADAP KONSEP DIRI DAN PRESTASI AKADEMIK MAHASISWA SEMESTER VIII SEKOLAH TINGGI ILMU KESEHATAN AISYAH PRINGSEWU - Triaristina, Aprilia (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2019)
A professional health worker can be established through an educational process. Students and education are two inseparable things. The quality of students can be seen from the academic achievement he achieved. Academic achievement is a change in behavioral skills or abilities that can increase over time that is not due to the growth process, but the existence of learning situations. So it is seen as proof of effort obtained by students. The number of samples in this study was 47 people. The results showed that. Most of the respondents who have self-concept in positive category are 31 respondents (65,9%), where there are 26 respondents (83,9%) got good academic achievement, and 5 respondents (16,1%) got poor academic achievement , And only 16 respondents (34.1%) have negative self concept, where as many as 7 respondents (43.8%) got good academic achievement, and as many as 9 respondents (56.2%) got poor academic achievement.